Explorando las bases pedagógicas de la gamificación como enfoque metodológico en la enseñanza superior - Villamar Gavilanes, Ana María (2024)
Gamification involves the application of game mechanics, dynamics, and components in non-game contexts. Its use in higher education has been increasingly prevalent. Despite the growing scientific literature on gamification, there is limited analysis of its pedagogical foundations. This article explores the conceptual definitions of gamification, along with the learning theories and motivations that underpin its use as a methodological approach in higher education. To achieve this, four research questions were formulated. The first examines the emerging conceptual frameworks of gamification, the second assesses its applications in educational settings, the third reviews the educational theories that support it, and the final question analyzes the benefits of gamification on learning outcomes. The findings indicate that gamification draws upon constructivism, connectivism, as well as the theories of self-determination and flow. Furthermore, its impact on motivation and learning is positively affirmed.